ChemInform Abstract: Synthesis and Disordered Crystal Structure of Al3O3.5C0.5. Issue 22 (13th May 2013) - Asaka, Toru; Kotani, Ryosuke; Kudo, Tatsunari; Yoshida, Hideto; Fukuda, Koichiro
Abstract The title compound is synthesized from a mixture of Al, Al2O3, and Al4C3 in a molar ratio of 3:5:2 (carbon crucible, argon, 2223 K, 1 h).